Physical activity and styles of coping with the stress of people aged 18-30 - Piepiora, Paweł; Jagoda, Alicja; Urban, Jerzy (Journal of Education, Health and Sport, 2019)
Aim: The aim of the research was to examine and demonstrate whether there are links between physical activity and styles of coping with stress, and to estimate with what force these possible relationships are manifested. Material and methods: 60 people aged 18-30 were randomly selected for the study. The first group consists of physically active persons, in which there were 12 women and 18 men, the second group were physically inactive persons with 21 women and 9 men. CISS was used - Questionnaire Coping in Stress Situations as a research method. The study used the Spearman's rank correlation as the basic statistical method. Results: Checked how physical activity correlates with a given style of coping with stress. The results of styles coping with stress within two groups of variables were compared. Conclusions: Physically active people differ from physically inactive people in terms of styles of coping with stress, within the style focused on emotions, the style focused on avoidance and the search for social contacts.